Perbandingan Konsep Integrasi Sains dan Agama Menurut Imam Prayogo dan M. Amin Abdullah - Rahmad Ramadhan; Eva Dewi; Syahrul Azmi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to find out the thoughts of Imam Prayogo and Amin Abdullah regarding the tree of knowledge and spider web models, to find out the differences in the thoughts of the two figures. By using data collection techniques in the form of studying and collecting data through reading materials sourced from primary books and secondary books related to the two figures discussed. This research uses a qualitative descriptive approach, and the type of research used is library research, namely collecting data or scientific writing aimed at the object of research or library data collection. From the research results, it was concluded that Imam Prayogo placed greater emphasis on the hierarchy and structure of knowledge rooted in revelation as the main foundation, with a focus on modernization and renewal of Islamic thought. Amin Abdullah, meanwhile, highlights the deep integration between Islamic and secular sciences in dealing with the complexities of contemporary life, placing the Qur'an and Sunnah at the center of his scientific framework.